Як спростити 7 + 2 (4x - 3)?

Як спростити 7 + 2 (4x - 3)?
Anonim

Відповідь:

# 8x + 1 #

Пояснення:

Помножте умови та додайте подібні терміни: -

# 7 + 2 (4x-3) = 7 + 8x-6 = 8x + 1 #

Відповідь:

# 7 + 2 (4x-3) = 1 + 8x #

Пояснення:

# 7 + 2 (4x-3) #

поширення #2# над умовами # (4x-3) #

#color (білий) ("XXXX") ## = 7 + (2) (4x) - (2) (3) #

виконуючи множення

#color (білий) ("XXXX") ## = 7 + 8x - 6 #

групування подібних термінів

#color (білий) ("XXXX") ## = (7-6) + (8x) #

виконання вирахування

#color (білий) ("XXXX") ## = 1 + 8x #

Відповідь:

Поширення #2#, потім спростити.

Пояснення:

# 7 + 2 (4x-3) #

Поширення #2#.

# 7 + 2 * 4x + 2 * -3 # =

Спростити.

# 7 + 8x-6 # =

# 8x + 1 #